Analysis of Real Hospital Cost on Ina-Cbgs Rates for Cesarean Section Patients - Wika, Wika Admaja; Kumala Sari Poespita D.W; Bhakita Ulyaziza A; Restyana, Anggi (Journal for Quality in Public Health, 2024)
A caesarean section is an artificial birth that is carried out by making a small incision in the abdominal wall and uterine wall, but the uterus must be intact and the fetus weighs >500 grams. The high cost of a cesarean section has prompted the Indonesian government to launch the National Health Insurance (JKN) program as an implementation of the National Health Insurance (JKN) which has been regulated regarding to the payment patterns to advanced health facilities by applying Indonesian Case Based Groups (INA-CBG's). This study aims to determine the difference between real hospital cost rates and INA-CBGs rates for payment of claims by JKN participants for caesarean section inpatients at Dr. Soedomo Regional Hospital Trenggalek. The research method is analytical observation with a cross sectional approach which refers to the hospital's perspective by comparing the direct medical costs of BPJS’s (Social Security Agency on Health) participant patients and the INA-CBG's rates. The populations of this study were BPJS recipients of class I, II, III inpatients who received mild category of caesarean section at Dr. Soedomo Regional Hospital Trenggalek in 2020. The sample used in this study was medical record documents that met the inclusion and exclusion criteria. Purposive sampling method was used. In treatment of I, II, III classes, a significant difference was found between the average total direct medical costs of mild category of caesarean section patients (O-6-10-I) compared to the INA-CBGs rates. The treatment of class I had a difference of IDR 886,582. (p<0.05). The treatment of class II had a difference of IDR 754,881. (p<0.05) and the treatment of Class III, the difference obtained was IDR 1,109,368. (p<0.05).